Preparation and physicomechanical properties of co-precipitated rice starch-colloidal silicon dioxide - Kittipongpatana,O.S. (Elsevier, 2015)
A new directly-compressible co-precipitated powder composing of rice starch and colloidal silicon dioxide (CSD) was prepared. The ratio of starch:CSD was tested at 8:1, 4:1, 2:1, 4:3 and 1:1, with three concentrations of sodium hydroxide (NaOH) (0.5, 1.0, 2.0. M) employed in the dispersion of CSD. Co-precipitated powders exhibited improved flowability, compactibility, superior bulk and tapped densities compared to that of native starch and physical mixtures. Scanning electron microscopic images showed adsorption of CSD on the surface of starch granules, while X-ray diffraction indicated that the granules remained crystalline. The moisture contents of co-precipitated powders were similar to that of native starch, while the moisture sorption at high relative humidity was affected only when the preparation was carried out with the use of 2.0. M NaOH. The optimum ratio of starch:CSD to yield powder with good flow and compactibility was found to be 4:1, with the use of either 0.5 or 1.0. M NaOH to disperse CSD. The results suggested potential application of rice starch-CSD co-precipitate in direct compression of pharmaceutical tablet. © 2011 Elsevier B.V.